Trust: A Bigger PictureTrust: A Bigger Picture, by WeickKarl E., Ann Arbor: University of Michigan. - Weick, Karl E. (Academy of Management Review, 2008)
The article reviews the book "Trust: A Bigger Picture," by Karl E. Weick.